2001
DOI: 10.1007/s003830000482
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal damage in gastroschisis is independent of the size of the abdominal defect

Abstract: The intestinal damage in gastroschisis (GS) has been attributed to a narrow abdominal wall defect (AWD), among other causes, but this causal effect is difficult to prove in humans. The present experimental study was done to ascertain the damaging effect of clinically extrapolable mild and moderate constriction at the AWD on the intestine of fetuses with GS. AWDs of two different sizes were carried out in the fetal rabbit model: small-ring GS (1.5x bowel diameter, SRG) and large-ring GS (3x bowel diameter, LRG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
10
1
4
Order By: Relevance
“…0.001). BW was not as altered in the subgroups (p = 0.793) as in the E18.5 and E19.5 groups (p = 0.271); these results are different from those of Albert et al [2] and FranchiTeixeira et al [27] who found a smaller BW in gastroschisis fetuses.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…0.001). BW was not as altered in the subgroups (p = 0.793) as in the E18.5 and E19.5 groups (p = 0.271); these results are different from those of Albert et al [2] and FranchiTeixeira et al [27] who found a smaller BW in gastroschisis fetuses.…”
Section: Discussioncontrasting
confidence: 56%
“…Experimental studies in which constriction of the vascular pedicle of the eviscerated bowel by a narrow AWD was analyzed to try to explain bowel thickening, edema and ischemic lesions have been made in chick embryo and lamb models, but their conclusions showed no relationship of intestinal changes with moderate or mild constriction at the site of the AWD [2] . These authors affirmed that there were no differences between constriction by an AWD 1.5 or 3 times the normal intestinal diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent studies it became clear that intestinal infl ammation was the consequence of several substances in the AF and not because of any ischemic injury [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Histology did not show venous stasis, ischemic lesions, or differences in the degree of edema between groups with a 2.6-mm ring compared to a 4.8-mm abdominal ring in a rabbit model. The conclusion was that intestinal changes in the length, weight, diameter, wall thickness, and histology in gastroschisis should not be attributed to the diameter of the abdominal wall defect [21]. In the rat and chicken model, meconium within the amniotic fluid has been associated with bowel damage.…”
Section: Pathologymentioning
confidence: 99%